A Critical Eye on a Prize: Unpacking the Meaning of "Applied Jewish Wisdom". Issue 4 (2nd October 2019) - Horowitz, Bethamie
ABSTRACT: The analysis examines the genesis of the Lippman-Kanfer Foundation for Living Torah's Prize in Applied Jewish Wisdom (AJW) that was first awarded in 2016. The foundation invented both the phrase AJW and the prize to highlight the qualities of Jewish content being employed by promising educators and activists in the "Jewish innovation ecosystem." This paper traces the emergence of the term in the writing of the foundation, and then delves in the sorting process undertaken by the foundation to determine the prize winners. AJW functions as a "boundary object." The Prize is a means of constituting AJW. The development of AJW positions the foundation to be able to claim "philanthropic authority" regarding a domain it wants to cultivate and champion. It is a way for LKFLT to assert its voice in the Jewish innovation sector and articulate a new rationale beyond simply funding innovation for its own sake.